2015
DOI: 10.3389/fmicb.2015.00056
|View full text |Cite
|
Sign up to set email alerts
|

Chemicals to enhance microalgal growth and accumulation of high-value bioproducts

Abstract: Photosynthetic microalgae have attracted significant attention as they can serve as important sources for cosmetic, food and pharmaceutical products, industrial materials and even biofuel biodiesels. However, current productivity of microalga-based processes is still very low, which has restricted their scale-up application. In addition to various efforts in strain improvement and cultivation optimization, it was proposed that the productivity of microalga-based processes can also be increased using various ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 92 publications
0
65
0
Order By: Relevance
“…Carotenoids are known to be major players of antioxidant response against ROS and found to be increased under metal stress (Yu et al, 2015). Significant decrement in phycocyanin content was noticed at all days of treatment under both Ni and As(III) stress in both species.…”
Section: Discussionmentioning
confidence: 91%
“…Carotenoids are known to be major players of antioxidant response against ROS and found to be increased under metal stress (Yu et al, 2015). Significant decrement in phycocyanin content was noticed at all days of treatment under both Ni and As(III) stress in both species.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, significant pH changes were also detected (Figure 1b). Observed results clearly show diauxic growth of E. gracilis [7]. Aeration rate and stirrer speed was also changed to promote optimal condition for microalgae cultivation and lipid production (Figure 2a & 2b).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to various efforts to improve growth and astaxanthin accumulation [5,6,13], as an alternative approach, chemicals, which served as metabolic triggers or enhancers that are able to directly adjust cellular metabolism, could be applied in H. pluvialis to improve production or accumulation of astaxanthin [14,15]. For example, reactive oxygen species (ROS), such as H 2 O 2 , 2,2′-azo-bis(2-amidinopropane)-dihydrochloride (AAPH) for peroxy radical (AO 2 •), methylene blue (MB) for singlet oxygen ( 1 O 2 ), and methyl viologen (MV) for superoxide anion radical (O 2 − ), were demonstrated to induce astaxanthin accumulation to about 50 pg/cell in H. pluvialis [16]; more recent studies showed that astaxanthin accumulation could be enhanced by jasmonic acid (JA), salicylic acid (SA), gibberellic acid (GA 3 ), abscisic acid (ABA) and 2,4-epibrassinolide (EBR); and the enhancing effects of the chemicals were concentration-dependent [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%